2009
DOI: 10.2190/ec.41.3.d
|View full text |Cite
|
Sign up to set email alerts
|

Using the Technological, Pedagogical, and Content Knowledge Framework to Design Online Learning Environments and Professional Development

Abstract: In this article we sought to understand how social studies teachers' metacognitive awareness of their technological, pedagogical, and content knowledge (TPACK) changed after their participation in a program that consisted of: (a) professional development for the use of an online learning environment; and (b) using an online learning environment in their classrooms. Inservice teachers who went through the TPACK-based program experienced considerable movement within the TPACK diagrammatic knowledge domains and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
101
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(119 citation statements)
references
References 17 publications
7
101
0
5
Order By: Relevance
“…Also, aligning with Roblyer and Doering (2010) and Doering, Veletsianos, Scharber and Miller (2009) we suggest that the TPACK framework need to be seen also as a tool for supporting (pre-service) teachers' reflective thinking. For this purpose, the instrument contains short scaffolding texts before each TPACK area aimed for outlining the core of that area and to help respondents to think and reflect better each area measured.…”
Section: Discussionsupporting
confidence: 73%
“…Also, aligning with Roblyer and Doering (2010) and Doering, Veletsianos, Scharber and Miller (2009) we suggest that the TPACK framework need to be seen also as a tool for supporting (pre-service) teachers' reflective thinking. For this purpose, the instrument contains short scaffolding texts before each TPACK area aimed for outlining the core of that area and to help respondents to think and reflect better each area measured.…”
Section: Discussionsupporting
confidence: 73%
“…The use of the TPACK framework in the context of the research study reported in this paper provides additional evidence of how the framework can be used to analyse online teaching practices within professional learning contexts, a process already instigated with social studies teachers by Doering, Veletsianos, Scharber, and Miller (2009). This paper reports on how the framework has been used specifically within a higher education context in which online teaching practices were the focus.…”
Section: Methodological Approachmentioning
confidence: 97%
“…TPİB modeline dayalı yapılan araştırmalarda, öğretmenlerin teknolojik, pedagojik içerik bilgilerinde özellikle teknoloji bağlamında kendilerini yetersiz hissettikleri ve teknoloji ile ilgili konularla uğraşmada kararsız oldukları görülmektedir (Archambault ve Crippen, 2009;Doering, Veletsianos, Scharber ve Miller, 2009). Bu sorunu aşmanın öğretmen adaylarının kendi eğitim programları içerisinde TPİB anlayışlarının geliştirilmesinden geçtiği öne sürülmektedir.…”
Section: Sonuçlarunclassified